Atomoxetine and fesoterodine combination improves obstructive sleep apnoea severity in patients with milder upper airway collapsibility. Issue 11 (10th July 2022) - Messineo, Ludovico; Taranto‐Montemurro, Luigi; Calianese, Nicole; Gell, Laura K.; Azarbarzin, Ali; Labarca, Gonzalo; Vena, Dan; Yang, Hyung Chae; Wang, Tsai‐Yu; Wellman, Andrew; Sands, Scott A.
Abstract: Background and objective: The combination of the noradrenergic atomoxetine plus the anti‐muscarinic oxybutynin acutely increased genioglossus activity and reduced obstructive sleep apnoea (OSA) severity. However, oxybutynin has shorter half‐life than atomoxetine and side effects that might discourage long‐term usage. Accordingly, we aimed to test the combination of atomoxetine and fesoterodine (Ato‐Feso), a newer anti‐muscarinic with extended release formulation, on OSA severity and endotypes. Methods: Twelve subjects with OSA underwent a randomized, double‐blind, crossover trial comparing one night of atomoxetine plus fesoterodine (80–4 mg) to placebo. Parameters of OSA severity (e.g., apnoea–hypopnoea index [AHI], nadir oxygen desaturation and hypoxic burden) were calculated from two clinical, in‐lab polysomnographic studies. OSA endotypes (including collapsibility per VMIN and arousal threshold) were derived from validated algorithms. Results: Compared to placebo, Ato‐Feso did not reduce the AHI (34.2 ± 19.1 vs. 30.1 ± 28.2 events/h, p  = 0.493), but reduced the apnoea index (12.9 [28.8] vs. 1.8 [9.1] events/h, median [interquartile range], p  = 0.027) and increased nadir desaturation (76.8 [8.0] vs. 82.2 [8.8] %, p  = 0.003); a non‐significant trend for improved hypoxic burden was observed (52.4 [50.5] vs. 29.7 [78.9] %min/h, p  = 0.093). Ato‐Feso lowered collapsibility (raised VMIN ; 43.7 [29.8–55.7] vs. 56.8 [43.8–69.8] %VEUPNOEA, mean [CI], p  = 0.002), but reduced the arousal threshold (129.3 [120.1–138.6] vs. 116.7 [107.5–126] %VEUPNOEA, p  = 0.038). In post hoc analysis, 6/6 patients with milder collapsibility (VMIN  > 43%) exhibited OSA resolution (drop in AHI > 50% and residual AHI < 10 events/h) and improved hypoxaemia. Conclusion: While inefficacious in unselected patients, Ato‐Feso administered for one night suppressed OSA in patients with milder collapsibility. Ato‐Feso may hold some promise as an alternative OSA treatment in certain subgroups of individuals. Abstract : We studied the combination of atomoxetine and fesoterodine (Ato‐Feso), an extended‐release anti‐muscarinic, on obstructive sleep apnoea (OSA) severity and endotypes. Despite the absence of an effect on OSA severity, Ato‐Feso led to improvements in OSA profile, reducing apnoea index and overnight hypoxaemia, especially in patients characterized by low‐to‐moderate pharyngeal collapsibility.